PHYSICO-CHEMICAL AND BACTERIOLOGICAL COMPOSITION IN A METROPOLITAN DRINKING WATER DISTRIBUTION SYSTEM IN KATHMANDU - Tamrakar, Pratima; Shakya, Suman K.; Baniya, Chitra B. (Journal of Institute of Science and Technology, 2017)
The study was concentrated on water quality appraisal in metropolitan drinking water distribution system in Kathmandu during 2011 to 2015 AD. The study covers 24 research areas from surface water sources, treatment plants, processing and water supply networks of public, private and community drinking water suppliers in the main city of Kathmandu valley. Water quality was analyzed under six physical, seventeen chemical and two bacteriological parameters. All tests were conducted in accordance with the procedures laid down in the Standard Methods. Total 320 samples collected during two years of periods. The physico-chemical parameters of tested water samples from sources, reservoirs and taps were found to be within the range of National Drinking Water Quality Standard (NDWQS). The turbidity and pH values for most of the tested water samples from sources, reservoirs and taps except for a few source and tap samples were found to be within the NDWQS guideline values. The chemical parameters values of majority of tested source water samples were below the maximum level. The values of iron, manganese, sodium and chloride content of some source samples were found higher than the maximum permissible level recommended by NDWQS and WHO guideline. Bacteriologically, larger proportion of water samples (sources, reservoirs and taps) were found to be unacceptable. The present study disclosed fecal contamination to be the major problem in drinking water from source to the distribution for city water supply systems in selected metropolitan areas. The physico-chemical qualities of water in most cases were within acceptable limit. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, page: 159-164